2006
DOI: 10.1111/j.1462-2920.2006.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nitrite reductase (nirK and nirS) genes and cultivation reveal depauperate community of denitrifying bacteria in the Black Sea suboxic zone

Abstract: Chemical profiles of the Black Sea suboxic zone show a distribution of nitrogen species which is traditionally associated with denitrification, i.e. a secondary nitrite maximum associated with nitrate depletion and a N(2) gas peak. To better understand the distribution and diversity of the denitrifier community in the Black Sea suboxic zone, we combined a cultivation approach with cloning and sequencing of PCR-amplified nitrite reductase (nirS and nirK) genes. The Black Sea suboxic zone appears to harbour a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 68 publications
(118 reference statements)
8
75
1
Order By: Relevance
“…All of the nirS sequences from this study clustered with sequences found in other studies of marine or estuarine sediment or water column (Jayakumar et al, 2004;Oakley et al, 2007), suggesting that the organisms detected in this study are typical of estuaries or are a result of tidal influx, rather than a result of terrestrial inputs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…All of the nirS sequences from this study clustered with sequences found in other studies of marine or estuarine sediment or water column (Jayakumar et al, 2004;Oakley et al, 2007), suggesting that the organisms detected in this study are typical of estuaries or are a result of tidal influx, rather than a result of terrestrial inputs.…”
Section: Discussionsupporting
confidence: 58%
“…Sequences from nirS libraries comprised 98 clones, grouping predominantly with sequences derived from studies of water column and estuarine sediments (Jayakumar et al, 2004;Oakley et al, 2007) (Figure 5). …”
Section: Diversity Of Nitrifiers and Denitrifiersmentioning
confidence: 99%
“…A similar tendency was observed in a salinity gradient in a beach aquifer at Huntington Beach (California) where different clades of nirK sequences were associated to specific salinities, whereas nirS did not show any specific environmental adaptation (Santoro et al 2006). Also, a recent study in the suboxic zone of the Black Sea (Oakley et al 2007) showed much greater variation of nirK sequences at the bottom of the suboxic zone, while nirS sequences were more homogeneously distributed.The nirS and nirK sequences from Lake Kinneret differed from those of marine habitats and coastal aquifers (Jayakumar et al 2004, Castro-Gonzalez et al 2005, Francis et al 2005, Santoro et al 2006). This suggests a differentiation of marine and purely freshwater denitrifying bacteria carrying nirS, but has to be substantiated by additional studies.…”
mentioning
confidence: 50%
“…The simultaneous amplification of nirS and nirK has been difficult in environments such as soil and sediments (Braker et al 2000, Avrahami et al 2002, Prieme et al 2002, Wolsing & Prieme 2004. In water samples, however, this seem to be possible (Oakley et al 2007). …”
mentioning
confidence: 99%
“…However, our results show that although the composition of nosZ-TRFs was positively correlated with O 2 , N 2 O and NH 4 + and negatively with NO 2 -there is not a clear trend in this aspect, suggesting that probably other variables not measured in this study, could also impact the structure of nosZ-type denitrifiers. For example, organic carbon, metal availability and also C:N and nitrate/ nitrite ratios have been reported to be important factors determining the community composition and structure of denitrifiers (Oakley et al 2007, Ward et al 2008, Mosier & Francis 2010.…”
Section: Discussionmentioning
confidence: 99%